New Antitumor Organotitanium Complexes with a Pendant Biologically Active Diazo Group - G. Arzoumanidis, Gregory (Fine Chemical Engineering, 2022)
The ligand of antitumor organotitanium or other metallodrug complexes plays a pivotal role in determining the mechanism of their cytotoxic action. Although the specific contribution of several ligands is generally well established, our understanding of the overall mechanism of the cytotoxic action of the complexes themselves is limited and incomplete in most cases, except perhaps in the case of cis-platin. A strategy to monitor the mode of cytotoxic action of candidate antitumor complexes requires tagging with bioactive side chains like a diazo group, for in-cell site-specific labelling. In this review we discuss new methods for the preparation of potential antitumor organotitanium complexes with a pendant diazo group, aiming at better understanding their mode of cytotoxic action. By introducing this new class of titanium-based potential antitumor agents, we hope to contribute to the world-wide effort in this important area of medicinal chemistry research, for an ultimate usable titanium-based antitumor drug. The following figure represents a model reaction depicting the methodology, for the formation of a bioactive Titanium complex with a pendant diazo group. Moreover, in this case, a scheme is required that represents all the possibilities of formation of the bioactive complex of titanium with a pendant diazo group.